EBV Associated Breast Cancer Whole Methylome Analysis Reveals Viral and Developmental Enriched Pathways - Abdallah, Mohammad O. E.; Algizouli, Ubai K.; Suliman, Maram A.; Abdulrahman, Rawya A.; Koko, Mahmoud; Fessahaye, Ghimja; Shakir, Jamal H.; Fahal, Ahmed H.; Elhassan, Ahmed M.; Ibrahim, Muntaser E.; Mohamed, Hiba S. (Frontiers in Oncology, 2018)
Background: Breast cancer (BC) ranks among the most common cancers in Sudan and worldwide with hefty toll on female health and human resources. Recent studies have uncovered a common BC signature characterized by low frequency of oncogenic mutations and high frequency of epigenetic silencing of major BC tumor suppressor genes. Therefore, we conducted a pilot genome-wide methylome study to characterize aberrant DNA methylation in breast cancer. Results: Differential methylation analysis between primary tumor samples and normal samples from healthy adjacent tissues yielded 20,188 differentially methylated positions (DMPs), which is further divided into 13,633 hypermethylated sites corresponding to 5339 genes and 6,555 hypomethylated sites corresponding to 2811 genes. Moreover, bioinformatics analysis revealed epigenetic dysregulation of major developmental pathways including hippo signaling pathway. We also uncovered many clues to a possible role for EBV infection in BC. Conclusion: Our results clearly show the utility of epigenetic assays in interrogating breast cancer tumorigenesis, and pinpointing specific developmental and viral pathways dysregulation that might serve as potential biomarkers or targets for therapeutic interventions.